HIFZ AL-‘IRDH (PROTECTING OF DIGNITY) AS THE BASIS FOR OFFENSES IN DOMESTIC CONFLICT - R. Dzihni Jawahir Labib; Nurul Afifah; Syahrul Anwar (Tunas Harapan Ummat Foundation, 2026)
Domestic conflict is often understood as a personal issue whose resolution is adequately placed within the realm of morality or family law. This view becomes problematic when conflict escalates into violence, coercion, or neglect that clearly violates the dignity and honor of family members, particularly in spousal relationships. This research aims to construct the principle of hifz al-'irdh within the framework of maqasid al-syari'ah as a normative and legal foundation for understanding domestic conflict and the conceptual justification for establishing family offenses, to analyze the relevance of maqasid al-syari'ah in responding to domestic violence practices, including sexual violence and forced abortion, and to bridge family law, criminal law, and Islamic law within an integrative framework oriented toward protecting human dignity and well-being. This research uses a normative legal research method with a conceptual approach to analyze legal doctrines and perspectives, a philosophical approach to explore fundamental values, and a comparison between Islamic law and Indonesian positive law. The main research sources include primary legal materials and secondary legal materials (legal literature, expert doctrine, scientific journals). Data collection techniques were carried out thru literature studies involving document searching and review. The data analysis techniques used were qualitative analysis to describe legal materials, interpretation using the hermeneutics method for an in-depth understanding of legal meaning, and comparative analysis to identify the alignment and differences in legal norms, as well as the implications of hifz al-'irdh for positive law. The research findings indicate that violations of dignity within the household (physical, psychological, sexual violence, reproductive coercion) are not only ethical or civil violations but also meet the criteria for serious violations of the objectives of Islamic law. The principle of hifz al-'irdh has a strategic function as a parameter for distinguishing domestic conflicts that are still in the private sphere from those that require criminal law intervention. This research concludes that integrating hifz al-'irdh into Indonesian family law and criminal law has the potential to strengthen the protection of human dignity, bridge Islamic law and national law, and promote legal reforms that are more oriented toward substantive justice and victim protection.